Reliability of the single leg stance test for safe removal of external fixator after tibial bone lengthening - Mahmoud El-Rosasy; Osama Elgebaly; Amr Elrosasy; Abdullah Khaled (Scientific Reports)
Abstract The timing of fixator removal in distraction osteogenesis is an important decision. Bipedal weight bearing may not be an accurate estimate of body weight distribution on both limbs. The purpose of this study was to test the reliability of the Single leg stance test (SLST) as an indicator of regenerate bone maturation and safe removal of the external fixator. Patients who underwent Ilizarov limb reconstruction for tibial bone lengthening were classified into two groups. The decision to remove the external fixator was based on radiological analysis and Bipedal walking in group A versus SLST in Group B. to be included in the study, the patient should be able to communicate, perform the test on the healthy limb, have no neuromuscular, visual or vestibular disorders, can do bipedal weight bearing unsupported and plain radiographs show at least three intact cortices. The data was collected retrospectively from 2012 to 2015 in group A and prospectively from 2016 to 2022 in group B. Interpretation of the test was done by two experienced surgeons in limb reconstruction and a junior orthopedic surgeon. A total of 50 patients and 52 patients were included in group A and B respectively. The inter-observer reliability of the three observers was almost perfect. Refracture after external fixator removal occurred in five cases in group A (10%) and one case in group B (1.9%). The SLST was able to predict regenerate maturation in 98% of cases in our series.The SLST is a simple, reproducible, and reliable clinical test that can be used to evaluate the maturation of the regenerate.